Personalized medicine in oncology: vision or realistic concept? - Lewandowski, Remigiusz; Roszkowski, Krzysztof; Lewandowska, Marzena Anna (Contemporary Oncology/Współczesna Onkologia, 2011)
Personalized medicine is often described as “the right treatment for the right person at the right time”. In order to better organize medical information systems and create a platform for personalized medicine the United States and the European Union have put into effect several regulations regarding the Electronic Health Record (EHR) system. A dramatic growth of the number of medical databases and medical data repositories, especially in the field of oncology, offers a great opportunity to apply data-mining for knowledge discovery. New high-throughput technologies that enable the exploration of complex oncological mechanisms appear promising in terms of earlier and more specific diagnostics, including data associated with the primary tumor site, the stage of disease, as well as treatment predictions. In addition, a broad application of data-mining as regards genetic and clinical information, and physical factors can substantially enhance individual therapy for each patient and potentially reduce the cost of cancer therapy.